Case report: Obstructive azoospermia as the first presentation of Von Hippel-Lindau disease - Scafa, Raffaele; Merico, Maurizio; Ferrara, Alfonso Massimiliano; Watutantrige Fernando, Sara; Srsen, Pava; Schiavi, Francesca; Zovato, Stefania; Ferlin, Alberto (Frontiers in Oncology, 2023)
We report the case of a 38-year-old man whose diagnostic workup for primary infertility led to the discovery of obstructive azoospermia due to bilateral papillary cystadenoma of the epididymis (PCE). Given the rarity of this finding and because PCE could be a manifestation of Von Hippel-Lindau disease (VHL), although the patient had no family or personal history of VHL, the VHL gene was tested, and a known pathogenetic variant (c.464-1G>A; p.)? was found. Screening for other Von Hippel-Lindau disease-associated neoplasms revealed bilateral retinal capillary hemangioblastomas, clear cell renal cell carcinoma, and multiple pancreatic cysts. In this case, an accurate diagnostic workup for male infertility allowed the detection of a rare life-threatening syndrome, already presenting with several silent neoplasms. For this reason, this case report may be useful for reproductive medicine specialists in the management of male infertility.